Value addition of tamarind: An option for livelihood of tribal people of Panchmahal (Indian Journal of Arid Horticulture, 2018)
Tribal rural families of district Panchmahals, Gujarat are living in poverty due to small holding size which is low in  productivity due to poor soil fertility and unavailability of irrigation facilities resulting in to subsistence farming. However, these  tribal families traditionally grow many minor fruit crops having drought tolerance especially tamarind and manila tamarind on the  fringes of their land; fruits of which they sold in the market at cheaper rates. KVK, Panchmahal has promoted value addition in  tamarind through training with the help of scientist of C.H.E.S., Godhra and N.G.O. Anandi for higher income generation.  Different types of value added products were made from tamarind fruits viz. tamarind puree, toffee and Oil polished tamarind  pulp. Study was carried out to determine the levels and preference range of ingredients in the various products to formulate recipes  of the products prior to processing and training the community members. The products made in this study were shown to be  viable, of good quality and good sources of income for rural tribal communities. As promotion of minor fruit crops like tamarind  without market linkage is risky, it is advisable to train the community for development of value added products so that they  generate more income from available resources and to avoid seasonal glut in the market.
Keywords: Tamarind; value addition; livelihood security